The YXXL signalling motifs of the bovine leukemia virus transmembrane protein are required for in vivo infection and maintenance of high viral loads. - Willems, L (1995)
The bovine leukemia virus (BLV) transmembrane protein (gp30) contains three YXXL motifs at its carboxyterminal end. Two of these motifs have been implicated in vitro in signal transduction pathways from the external to the intracellular compartment. In order to analyze the biological relevance of these motifs in vivo, recombinant BLV proviruses were constructed. A mutation of the tyrosine residue of the second YXXL motif completely destroyed the infectious potential of the virus in sheep. In contrast, the tyrosine of the first motif appeared to be dispensable for infectivity. However, the propagation of the recombinant virus within the animal was greatly impaired (as demonstrated by PCR and enzyme-linked immunosorbent assay). These recombinant BLVs thus exhibit an attenuated phenotype. Altogether, our data demonstrate the importance of the YXXL motifs of the BLV transmembrane protein for in vivo infection and viral propagation.